Pengaruh Penggunaan Fly Ash dari Berbagai Sumber terhadap Sifat Kimia dan Sifat Fisika pada Semen Tipe I (OPC) - Yusuf, Yulizar; Savitri, Vivin Firman; Aziz, Hermansyah (Jurnal Riset Kimia, 2020)
The aim of this study is to utilize fly ash from various sources on chemical and physical properties of cement type I (OPC). Utilization of fly ash can improve the strengthness of the cement. It can reduce the waste of fly ash by utilization into cement process. The procedure has been carried out on cement type I (OPC) with the addition of fly ash additives from various sources with concentration variations such as 10% and 20%. Utilization of fly ash as additives substance in cement works to improve the quality of cement. The main parameter in determining the quality of cement is determined by the compressive strength. The results of the compressive strength test showed that the addition of fly ash with a concentration of 10% had a higher effect on the compressive strength than the addition of a concentration of 20%. 5 types fly ash from various sources, fly ash from PT Sinar Mas gives greater compressive strength at 28 days. the addition of fly ash additives to OPC cement mixture has chemical and physical properties which are not much different from properties of PCC cement.